Domesticated chickens interact more with humans and are more explorative than Red Junglefowl - Demree, Ruth; Jensen, Per (Frontiers in Veterinary Science, 2025)
Domesticated species are adapted to thrive in an environment with regular human interaction, and these interactions influence the development of a human-animal relationship. Chickens are the most abundant domesticated species, but their relationship with humans is poorly understood. A more comprehensive analysis of this relationship would provide valuable insight into their welfare needs. The present study compares the behavior of a domesticated and a non-domesticated breed of Gallus gallus in the presence of a familiar human. The domesticated breed was more active overall, and displayed more human contact-seeking behavior. These behavioral differences contribute to our understanding of the human-chicken relationship and could be helpful new insights for improving welfare of chickens in agricultural practice.